Pengaruh Prestasi Coaching, Konseling, dan Mentoring Terhadap Kinerja Guru Penggerak Angkatan II di Kabupaten Kebumen - Nur Hidayati (Media Manajemen Pendidikan, 2023)
This study aims to examine and analyze (1) the effect of coaching, counseling, and mentoring, together on teacher performance, (2) the effect of coaching on teacher performance, (3) the effect of counseling on the performance of  teacher, ( 4) the effect of mentoring on teacher performance. This type of research uses a quantitative approach method. The population of this study were Kindergarten, Primary School, Junior High School, and Senior High School teachers who took part in the 2nd batch of Teacher Mobilization Education in Kebumen Regency, totaling 147 people.     Data collection techniques using a questionnaire. Data collection techniques for major hypotheses using multiple linear regression analysis and minor hypotheses with partial correlation. The results of this study indicate that: (1) There is a positive and significant effect of coaching, counseling, and mentoring together on teacher performance, (2) There is a positive and significant influence of coaching on the performance of the teacher, (3) There is a positive and significant influence of counseling on the performance of the teacher, (4) There is a positive and significant influence of mentoring on teacher performance. Of the three independent variables that have a dominant influence on the performance of the teacher performance is coaching.